Passivation-driven speciation, dealloying and purification. Issue 3 (26th January 2021) - Martin, Andrew; Chang, Boyce; Cutinho, Joel; Shen, Liyang; Ward, Thomas; Cochran, Eric W.; Thuo, Martin M.
Abstract : Kinetics of passivating oxide growth can drive nanoscale surface order/speciation. Combined with oxide growth and thermal expansion, trapped oxide crystals ('ship-in-a-bottle') or extrusion of metal fingerlings ('spiky particles') can be achieved. Abstract : Thin passivating surface oxide layers on metal alloys form a dissipation horizon between dissimilar phases, hence harbour an inherent free energy and composition gradient. We exploit this gradient to drive order and selective surface separation (speciation), enabling redox-driven enrichment of the core by selective conversion of low standard reduction potential ( E °) components into oxides. Coupling this oxide growth to volumetric changes during solidification allows us to create oxide crystallites trapped in a metal ('ship-in-a-bottle') or extrusion of metal fingerlings on the heavily oxidized particle. We confirm the underlying mechanism through high temperature X-ray diffraction and characterization of solidification-trapped particle states. We demonstrate that engineering the passivating surface oxide can lead to purification via selective dealloying with concomitant enrichment of the core, leading to disparate particle morphologies.